Beyond Pollination: Honey Bees (Apis mellifera) as Zootherapy Keystone Species - Easton-Calabria, August; Demary, Kristian C.; Oner, Nola J. (Frontiers in Ecology and Evolution, 2019)
The keystone species concept is a useful ecological concept to explain how some species exert a strong force on their community structure; this paper strives to expand the definition to include species that are used in zootherapy, i.e., the use of animals for medicinal purposes. Honey bees (Apis mellifera) can be considered a zootherapy keystone species that exerts a strong impact on other trophic levels through their products that relate to disease resistance. Honey bee products (i.e., honey, propolis, venom, beeswax, bee bread, and royal jelly) confer pathogen/pest resistance. Each of these products have been shown to exhibit antipathogenic properties and to act as a colony-level defense mechanism against disease. The phenomenon of a collective immune defense in social insects, termed social immunity, has evolved for defense against pathogens which spread easily in highly dense eusocial systems, such as that of honey bees. In apitherapy, a type of zootherapy, humans can use honey bee products to improve their health via pathogen resistance. The implication of these phenomena is that honey bees, through their products, can manipulate the microbial community structure both within the hive and outside the hive when these products are used in apitherapy. Because of their importance to human health, zootherapy keystone species should be a top priority in terms of conservation.